2018
DOI: 10.1299/transjsme.17-00365
|View full text |Cite
|
Sign up to set email alerts
|

Study on acoustic natural frequency and its mode of one dimensional sound field partitioned by perforated plate

Abstract: Karman vortex shedding occurs when the gas passes through the duct with tube bank of the heat exchangers, such as gas heaters and boilers. Very high level sound in called "self-sustained tones" occurs due to the interference of the vortex and the sound field in the duct. In general, baffle plates are used to suppress the self-sustained tone. However, it is difficult to use them effectively, because insertion conditions have not been established. Then, perforated plates are installed in both sides of the duct t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Table 2 represents the peak frequency in each case of the aperture ratio. It has been also confirmed that the resonance frequency increases as the aperture ratio increases in the previous study [31] in which an acoustic resonance frequency has been experimentally and analytically verified by assuming a one-dimensional sound field in a duct partitioned by a perforated plate, and similar results are obtained in this study. Figure 33 shows the acoustic mode at each peak frequency in the cases of ϕ = 0, 1, 2, and 4%.…”
Section: Acoustic Simulations and Suppression Mechanism Of Self-sustasupporting
confidence: 89%
“…Table 2 represents the peak frequency in each case of the aperture ratio. It has been also confirmed that the resonance frequency increases as the aperture ratio increases in the previous study [31] in which an acoustic resonance frequency has been experimentally and analytically verified by assuming a one-dimensional sound field in a duct partitioned by a perforated plate, and similar results are obtained in this study. Figure 33 shows the acoustic mode at each peak frequency in the cases of ϕ = 0, 1, 2, and 4%.…”
Section: Acoustic Simulations and Suppression Mechanism Of Self-sustasupporting
confidence: 89%
“…The mode orthogonality as shown in the equation (11) is even true for the case of one dimensional sound field partitioned with the perforated plate. Figure5 (a) and (b) are 1 st mode and 2 nd mode shapes of the pressure obtained by the reference [6] respectively. The horizontal axis shows the position from the origin and the vertical axis shows the normalized sound pressure.…”
Section: Consider the Viscous Coefficient C (N・smentioning
confidence: 99%
“…A perforated plate is widely used as an acoustic absorption material for compressors [1] and acoustic barriers for roads and railways [2]. It has been confirmed that the perforated plate suppressed the self-sustained tone generated from heat exchangers like a boiler by using it on a duct wall [3][6]. The effects of the perforated plate on the acoustic natural frequency of an one dimensional sound field partitioned with the perforated plate has been studied in our previous investigations [7], [8].…”
Section: Introductionmentioning
confidence: 99%